2017
DOI: 10.3390/su9020199
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services and Ecological Restoration in the Northern Shaanxi Loess Plateau, China, in Relation to Climate Fluctuation and Investments in Natural Capital

Abstract: Accurately identifying the spatiotemporal variations and driving factors of ecosystem services (ES) in ecological restoration is important for ecosystem management and the sustainability of nature conservation strategies. As the Green for Grain project proceeds, food provision, water regulation and climate regulation services in the Northern Shaanxi Loess Plateau (NSLP) are changing and have caused broad attention. In this study, the dynamic pattern of the normalized differential vegetation index (NDVI) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 64 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…These studies then estimated the impact of land use changes to ESs via scenario simulation or correlation analysis [26][27][28][29][30]. Wei et al [28] quantified the change in CS using the Carnegie-Ames-Stanford approach (CASA) model and found that although afforestation decreased the cropland area in the Northern Shaanxi Loess Plateau, the CS increased because of investments in natural capital (i.e., afforestation, chemical fertilizer, and agricultural machinery power). Except individual ESs, a few studies have found that ES bundles are linked to land use [30,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies then estimated the impact of land use changes to ESs via scenario simulation or correlation analysis [26][27][28][29][30]. Wei et al [28] quantified the change in CS using the Carnegie-Ames-Stanford approach (CASA) model and found that although afforestation decreased the cropland area in the Northern Shaanxi Loess Plateau, the CS increased because of investments in natural capital (i.e., afforestation, chemical fertilizer, and agricultural machinery power). Except individual ESs, a few studies have found that ES bundles are linked to land use [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Biophysical methods are usually applied to analyze the relationships between land use changes and ESs, but the results of most studies in the field do not meet the information requirements of decision makers and have not yet been incorporated into the relevant policy decisions given that these results do not take into account the perspectives of local stakeholders [16,18,20,26,28,30]. Given that biophysical methods are unable to capture the perceptions of local residents toward ESs and land use change, multidisciplinary approaches, including biophysical and sociocultural methods, must be applied to understand the relationships between ESs and land use change.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of these changes result in the degradation of ESs, which is the aggregate of ecosystem goods (such as food) and services (such as waste assimilation), that represent the benefits human populations derive, directly or indirectly, from ecosystem functions [12]. These impacts make the quantification of Ecosystem Service Values (ESVs) essential to raise awareness [13], develop decision making for the distribution of scarce resources among conflicting demands [14], incorporate ESs into the socioeconomic and marketing systems [15], formulate policy [16] and stimulate the conservation of ecosystems that deliver the most valuable services in support of human well-being [17].Following the pioneering works of Costanza et al [18], who estimated global ESVs by suggesting a list of ESV coefficients for different biomes, the evaluation of ESVs and their changes has received broad attention [15,16,19]. Since then, to support mitigations of local degradation and global change problems, the interest in the valuation of ESs has grown rapidly in research and policy making communities.…”
mentioning
confidence: 99%
“…The consequences of these changes result in the degradation of ESs, which is the aggregate of ecosystem goods (such as food) and services (such as waste assimilation), that represent the benefits human populations derive, directly or indirectly, from ecosystem functions [12]. These impacts make the quantification of Ecosystem Service Values (ESVs) essential to raise awareness [13], develop decision making for the distribution of scarce resources among conflicting demands [14], incorporate ESs into the socioeconomic and marketing systems [15], formulate policy [16] and stimulate the conservation of ecosystems that deliver the most valuable services in support of human well-being [17].…”
mentioning
confidence: 99%
“…Ecosystem services, the goods and services that ecosystems provide for human well-being (Alcamo et al 2003;Millennium Ecosystem Assessment (Program) 2005), are increasingly used as a framework worldwide for the purposes of ecological restoration and conservation (Wei et al 2017), watershed management (Falkenmark et al 2004), and sustainable development policy making (Asbjornsen et al 2015). Among the myriad of services provided by ecosystems, hydrological services such as water purification and water supply are considered the key to realizing other ecological services such as drinking water, recreation, and human health (Brauman et al 2007;Keeler et al 2012).…”
Section: Introductionmentioning
confidence: 99%